Global generic competences with local ownership: a comparative study from the perspective of graduates in four world regions - Pablo Beneitone; Edurne Bartolomé (Universidad de Deusto, 2014)
The article addresses the issue of generic competences across different cultural contexts in the world. Using the Tuning projects data collected in Europe, Latin America, Africa and Russia, and focusing on graduates´ perspective, the authors aim to classify and compare the list of generic competences throughout all geographic regions covered by Tuning, analyse the importance and achievement given to the generic competences throughout different contexts, and also contrast the latent constructs obtained from the exploratory factor analysis, in order to observe how competences are classified and clustered across regions. The article shows and explains the main differences observed and stresses the relevance of taking into account the cultural context and the traditions of education systems, in order to properly understand the importance of generic competences in different regions, and also how, even though the competences are equivalent, they may articulate distinctive dimensions in each region.